English Teachers’ Challenges In Online Teaching English at State and Private Senior High School In Bengkulu City - Fikriyah, Anisah; Susyla, Dian (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The aims of this research were to find out and describe the English teachers` challenges in online teaching English at state and private senior high school in Bengkulu City. The design of this research was descriptive qualitative method. The subjects of this research were English teachers while The data collected from interviewing the English teachers and recorded the interview. The result of this research showed that most of the teachers had the similar challenges in online teaching English including in planning process, implementing process and evaluating process. In planning process, six from seven teachers were difficult to choose the appropriate online teaching media for students. In implementing, the difficulty are in the term of handling the students` focus or attention, unstable internet connection, students` low motivation and students low mastery in operating the online learning`s platforms. For evaluating process, the teachers are unsure if the students do the assignment by themselves or not, the students also did not collect the assignments on time and one of the teachers in State Senior high School also said that he had problem in doing affective assessment. The results of this research are expected to be useful for English teachers to anticipate challenges that might be faced by teachers in online teaching English both in state and private Senior High Schools.Keywords: Teachers Challenges, Online Teaching English, Pandemic Covid-19